Evolution of the Pseudo-Components of Heavy Oil during Low Temperature Oxidation Processes - Zhao, Renbao; Wang, Tiantian; Chen, Lijuan; Pan, Jingjun; Li, Shutong; Zhao, Dong; Chen, Long; Wang, Jiaying (Energies (Basel), 2022)
Heavy oil was divided into different pseudo-components according to their boiling ranges through a real-boiling point distillation process, and the oxidation products for pseudo-components with a boiling range higher than 350 °C were systematically investigated during low temperature oxidation (LTO). Kinetic cell (KC) experiments were conducted under different ambient pressure conditions and temperature ranges, and the oxidation products were characterized using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). The results indicate that the oxygen addition and cracking reactions typically occur in the temperature intervals of 140–170 °C and 180–220 °C, respectively, at the given heating rate of 3.83 °C/min. Components with the mass-to-charge ratio in the region of 250–450 Da mainly evaporate in the temperature regions of 25–150 °C, which results in losses from the fraction. Considering the gas-liquid multi-phase reaction, the pseudo-components with low boiling range distributed on the surface of the liquid film are prone to generate high molecular weight compounds through oxygen addition. In contrast, the high boiling point range fractions increase in molecular weight through oxygen addition and are then subject to further cracking processes that generate lower molecular weights in the region of 200–400 Da. N1O3- and N1O4- containing compounds were determined by high resolution mass spectra, and these compounds were generated through oxygen addition of basic N1-containing compounds. On the basis of these reactions and the experimental results obtained, some insights related to the LTO of heavy oil, which are highly valuable for ISC field applications, are summarized.